Internalized and externalized problems in preschoolers and emotional state of caregivers during the COVID-19 pandemic: A longitudinal study - Herazo Chamorro, Mónica Isabel; Pérez Vásquez, Diego Armando; Bolaños-Torres, Bertha Isabel; Fonseca Beltrán, Leodanis Danith; Romero-Acosta, Kelly Carolina (Gaceta Médica de Caracas, 2023)
Introduction: The COVID-19 pandemic forced to take measures to protect public health such as mandatory social isolation and the closure of universities and schools, unprecedented measures such as the case of Colombia that affected the emotional state of the population and their mental health. Objective: To compare internalized and externalized problems in preschoolers and the emotional state of caregivers during the COVID-19 pandemic, at three different times, before isolation (2019), during isolation (2020) and after it (2021).